2016
DOI: 10.1002/jat.3384
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of 4‐methylthio‐3‐butenyl isothiocyanate (Raphasatin) in the rat urinary bladder without genotoxicity

Abstract: We recently reported that 4-methylthio-3-butenyl isothiocyanate (MTBITC) exerts chemopreventive effects on the rat esophageal carcinogenesis model at a low dose of 80 ppm in a diet. In contrast, some isothiocyanates (ITCs) have been reported to cause toxic effects, promotion activity, and/or carcinogenic potential in the urinary bladder of rats. In the present study, we investigated whether MTBITC had toxic effects in the urinary bladder similar to other ITCs, such as phenethyl ITC (PEITC). First, to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Regarding cell cycle arrest, previous studies have found that sulforaphene inhibits proliferative activity by increasing the expression of p21 (cyclin-dependent kinase inhibitor), which in turn promotes G1 cell cycle phase arrest (esophageal carcinogenesis in vivo). By contrast, sulforaphene induces apoptosis through increased expression of p21 (32), downregulation of the B-cell lymphoma-2 (Bcl-2)/apoptosis regulator BAX (Bax) ratio (in vivo) and activation of caspase-3 and -9 (in vitro, A549 lung cancer cells) (46). In the present study, few apoptotic cells were observed following 3-BI treatment of PC-3 cells, suggesting that the effect of 3-BI could be mediated through other pathways, which will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding cell cycle arrest, previous studies have found that sulforaphene inhibits proliferative activity by increasing the expression of p21 (cyclin-dependent kinase inhibitor), which in turn promotes G1 cell cycle phase arrest (esophageal carcinogenesis in vivo). By contrast, sulforaphene induces apoptosis through increased expression of p21 (32), downregulation of the B-cell lymphoma-2 (Bcl-2)/apoptosis regulator BAX (Bax) ratio (in vivo) and activation of caspase-3 and -9 (in vitro, A549 lung cancer cells) (46). In the present study, few apoptotic cells were observed following 3-BI treatment of PC-3 cells, suggesting that the effect of 3-BI could be mediated through other pathways, which will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…1). ITCs have inhibitory effects on the metabolic activation of carcinogenic dietary or tobacco components (24), along with the inhibition of mutagenesis (25) and anti-carcinogenic effects in vitro (26)(27)(28)(29)(30) and in vivo (31,32). In PC, ITCs modulate epigenetic changes, induce the arrest of the cell cycle, activate apoptosis pathways and increase chemotherapeutic agent sensitivity; leading to the inhibition of cell proliferation, progression and invasionmetastasis (33).…”
Section: Introductionmentioning
confidence: 99%
“…The two isothiocyanates occur with similar abundance to one another and in comparisons with broccoli sprouts for bioactivity, radish sprouts are similarly potent. Also of interest is that radishes are mostly devoid of ESP and thus generate higher yields of isothiocyanate without special pretreatments …”
Section: Chemistry Bioavailability and Metabolism Of Cruciferous Vementioning
confidence: 99%
“…PEITC proved positive in micronucleus induction assays with human‐derived HepG2 cells and in chromosomal aberration or sister chromatid exchange tests with Chinese hamster ovary cell lines in vitro (Musk et al, ; Kassie and Knasmuller, ). Recently, we revealed that treatment with PEITC for 3 days at doses of 90 mg kg −1 body weight by gavage to rats caused no increase in the parameters of the comet assay in the urinary bladder and micronucleus assays in the bone marrow (Suzuki et al, ). Additionally, excessive doses of BITC did not induce DNA damage in the rat urinary bladder or liver in in vivo comet assays (Wada et al, ).…”
Section: Discussionmentioning
confidence: 99%